Human-biometeorological effects on sleep disturbances in Athens, Greece: A preliminary evaluation - Nastos, P. T.; Matzarakis, A. (Indoor and Built Environment, 2008)
The aim of this study was to examine the effects of the daily minimum air temperature and human-biometeorological variables, as well as their day-to-day changes, on sleep disturbances (SD) in the inhabitants of Athens, Greece. The SD dataset used for the analysis included the daily records of the psychiatric emergency unit of the Athens University Medical School for the years 1989 (with mild thermal load) and 1994 (with heavy thermal load). The meteorological variables for the estimation of the thermal indices were recorded by the meteorological station of Hellenikon, which is located at the headquarters of the Hellenic National Weather Service. The mean radiant temperature (T mrt) and the thermal indices predicted mean vote (PMV), physiologically equivalent temperature (PET) and standard effective temperature (SET*) have been analyzed. The first step was to assess the SD frequencies as a function of the meteorological and human-biometeorological variables on the basis of 10-day intervals to determine the influence of the examined variables on SD. The daily SD records were included as Poisson random variables in the applied Generalized Linear Models (GLM). The extracted results suggested that a considerable increase in SD existed in 1994 compared to 1989. This was due to the many consecutive days with heavy thermal load (PET >35°C and Tmin >23°C) in 1994 compared to the lack of such days in 1989. Furthermore, statistically significant (p<0.01) positive relationships were found between minimum air temperature, all thermal indices and SD. © SAGE Publications 2008.
Keywords: air temperature; article; Athens; data analysis; emergency ward; Greece; Minimum air temperature; Poisson distribution; priority journal; sleep disorder; Sleep disturbances; statistical significance; Thermal indices